Observation of a Possible Successful Treatment of DEPDC5-Related Epilepsy with mTOR Inhibitor - Hadzsiev, Kinga; Hegyi, Márta; Fogarasi, András; Bodó-Baltavári, Tímea; Zsigmond, Anna; Maász, Anita; Szabó, András; Till, Ágnes (Neuropediatrics, 2023)
The mechanistic target of the rapamycin signaling pathway serves as a central regulator of cell metabolism, growth, proliferation, and survival. In its regulation, the GTPase-activating protein activity toward Rags1 complex has an inhibitory effect. Mutations in genes encoding this complex protein are among the most common abnormalities in focal epilepsies. Within these mutations, the mutations affecting the DEPDC5 gene have been associated with different autosomal dominantly inherited epilepsy types. Due to the limited data available on mTOR inhibitor therapy in nontuberous sclerosis complex epileptic patients, here we present the clinical management of a patient with intractable epilepsy, skin hypopigmentation, and a DEPDC5 variant. The patient's phenotype is compatible with a nonlesional DEPDC5-related epileptic encephalopathy. We initiated compassionate, off-label everolimus treatment as the patient's condition continuously deteriorated. Due to bilateral pneumonia occurring at the beginning of the treatment, it was temporarily discontinued, and resumed in half the dose. Follow-up examination after 18 months showed a 90% reduction in seizure frequency with moderate improvement in attention function and nutritional status. Our case report emphasizes the importance of early genetic testing in patients with epileptic encephalopathy. Clinical consequences of mammalian target of rapamycin complex 1 (mTORC1) upregulation may be amenable to tailored treatment with mTOR inhibitors. A clinical trial on an international scale would be needed to draw conclusions.
Keywords: epilepsy; GATOR complex; DEPDC5 gene; everolimus; hypopigmentation